CORPORATE SOCIAL RESPONSIBILITY (CSR) ACTIVITIES OF PT. ANGKASA PURA II HALIM PERDANA KUSUMA IN MAINTAINING THE COMPANY'S IMAGE - Maarif; Setiawati, Ni Made Wahyuni; Prihapsari, Yuvani (Jurnal Komunikasi dan Bisnis, 2022)
PT Angkasa Pura II (Persero) Halim Perdana Kusuma Airport branch as one of the SOEs within the Ministry of Transportation which is active in the field of business and service services. Various efforts made by PT Angkasa Pura II (Persero) Halim Perdana Kusuma Airport branch in improving the company's positive image in the eyes of the public. The concepts used in this study include the Concept of Marketing Communication, the Concept of Public Relations, the Concept of Corporate Social Responsibilty, and the Concept of Corporate Image. The object of this study is PT. Angkasa Pura II (Persero) branch of Halim Perdana Kusuma Airport. The results of the study found that pt. Angkasa Pura II (Persero) branch of Halim Perdana Kusuma Airport in the field of education includes providing educational scholarships, library cars, lab construction. Computers, stationery provisions, as well as marching band tools. Meanwhile, free treatment, cleft lip surgery, cataract surgery and mass circumcision, are programs in the health sector. Furthermore, in the field of partnership in the form of business capital assistance and assistance for fostered partners as well as training / education. However, in image management, it can not only be done through CSR activities. Obtained from the results of interviews, the media also plays an important role in its influence on the formation of the company's image in the minds of the public. CSR programs that have been carried out are also not always able to fulfill the wishes of CSR recipients. Every CSR activity also always starts by looking at the feasibility of the proposal submitted to the company.